Non-specific immune responses of the Indian major carp Labeo rohita Hamilton to infestation by the freshwater fish louse Argulus siamensis (Wilson) - Shailesh, Saurabh; Sahoo, P K (Indian Journal of Fisheries, 2016)
The study was undertaken to evaluate the non-specific immune responses of the Indian major carp, Labeo rohita naturally infested with different loads of the freshwater fish louse, Argulus siamensis. Results showed that glucose level and total antiprotease activity of serum were significantly higher in fish with different degrees of lice infestation, compared to uninfested control fish. Complement and Î±-2 macroglobulin activities were significantly (p<0.05) lower in lice-infested fish as compared to uninfested control fish. No significant canges were noticed in the NBT assay, myeloperoxidase activity, lysozyme activity, ceruloplasmin activity, haemolysin titre and packed cell volume recorded in the uninfested control fish and lice infested fish. The total protein and haemagglutination titres were not significantly different in fish infested with moderate and high levels of the lice as compared to uninfested control fish. However, a higher value of glucose level, NBT activity and total antiprotease level were observed in lice-infested female fish compared to their respective control fish. The alternate complement activity (ACH50) natural haemolysin and haemagglutination titres were significantly lower in lice-infested female fish as compared to uninfested female fish. In lice-infested male fish ceruloplasmin level was lower and total protein was significantly higher as compared to respective control fish. The present study also showed a positive correlation of blood glucose level, total antiprotease, NBT and myeloperoxidase activities with the degrees of lice infestation. The results of the study indicate that fish immune system particularly of female fish is significantly influenced by Argulus infestation.